Phonological Inadequacies in the Pronunciation of Three-Syllable Words by University EFL Learners - Yousif, Mukhalad Malik (The Scientific Journal of Cihan University– Sulaimaniya, 2020)
To communicate with each other, pronunciation is a prerequisite for such a crucial activity to occur. But there is no doubt that pronunciation plays a significant role in the process of communication as far as an efficient and a successful mutual interaction and understanding are concerned. This is largely the case when people of two different language backgrounds communicate. Part of such communication is the pronunciation of words which are usually made up of a sequence of sounds produced together. To fully understand the pronounced words, their pronunciation should be efficient or at least have the minimum requirement of pronunciation acceptance. The current article focuses on identifying the production level of pronunciation by university EFL learners of English words which comprise three- syllables being more challenging and complex. To achieve the purpose of the study, a theoretical survey of syllables is introduced being an essential part of understanding how such words are pronounced. Indeed, syllables in English are one of the most important topics that play a major role in mastering an efficient performance of the way English words are pronounced. A test is prepared to identify the level of pronunciation of such words by the learners. The goal of the test is to investigate whether the three-syllable words are pronounced adequately or inadequately. The test comprises a group of three-syllable words given to learners on printed forms which are later compared to the native pronunciation so as to compare between each. The article explicitly shows that university learners fail to pronounce such words adequately or, at least, they don’t phonologically possess the acceptable requirements for the pronunciation of such words. More specifically, the results show that such failure is due to certain phonological attributes including mainly the inadequate stress placement, inadequate vowel reduction and severe lack of phonological knowledge.